The role of disturbance and local adaptation in altering tree regeneration responses to climate change - Nigro, Katherine M., author; Redmond, Miranda D., advisor; Battaglia, Michael A., committee member; Stevens-Rumann, Camille S., committee member; Rocca, Monique E., committee member (Colorado State University. Libraries, 2023)
Anthropogenic climate warming is predicted to reorganize the communities seen on the landscape today as species migrate to stay within their preferred climate niche. However, for long-lived trees, it is uncertain whether migrations will be able to keep pace with the rapidly changing climate. In addition, adaptations to local climate that have evolved within subpopulations of a species may become obsolete or maladaptive under climate change. Natural disturbances such as wildfire and insect outbreaks in forests may help to accelerate range shifts by reducing competition from other plant species and creating favorable microsites for establishment of novel species. For landscapes that are not recovering after disturbance events, human-assisted movement of populations within species (assisted gene flow) has been proposed to pre-adapt the forest to future climate conditions. In the first part of my dissertation, I analyze large-scale USDA Forest Service Forest Inventory and Analysis data from the interior western US and conduct a field study of trembling aspen in southern Colorado to understand how disturbances are interacting with climate change to alter species range shifts at broad and local scales. The first chapter of my dissertation shows that disturbances are catalyzing range shifts on a large-scale for the dominant tree species of the interior western US under both disturbed and undisturbed conditions, but mostly through reduced regeneration in hot and dry portions of species ranges rather than expansions into cooler and wetter areas. However, chapter 2 reveals that expansions are happening on more local scales for trembling aspen after wildfire, but not after beetle-kill mortality events. Therefore, this research shows that disturbance-facilitated species range expansions are limited to certain species and locations, which may not be enough to keep pace with climate warming. The second part of my dissertation investigates the potential for assisted gene flow in ponderosa pine by examining differences between seedlings from different populations and mother trees in both the greenhouse under drought and the field under a variety of microsite conditions. This research reveals that population climate and watering regime are important determinants of seedling growth in the greenhouse, but that ponderosa pine seedlings from hotter and drier populations do not possess adaptations typically associated with drought-tolerance and do not perform well when planted at the cooler range margin. In addition, mother tree sensitivity to climate was influential in seedling water use efficiency in the greenhouse and in the sensitivity of seedlings to microclimate conditions in the field, making the case that targeting seed collections from specific mother trees may be warranted. Overall, my dissertation research provides insight into how future disturbance events are likely to influence regeneration at species range margins and provides valuable information for land managers seeking to implement assisted gene flow at the upper elevational margin of ponderosa pine forests.